The Association between the Perception of Aging and Functional Independence in the Elderly Patients with Type II Diabetes Mellitus - F Bastani; P Beigi Boroujeni (Iran University of Medical Sciences, 2019)
Background & Aims: Diabetes mellitus (DM) affects 4.5 million individuals in Iran. DM has a chronic, progressive nature and is associated with long-term complications, which adversely affect health due to the adoption of improper coping mechanisms, stemming from the psychological factor of ageing perception. The present study aimed to determine the correlation between the perception of aging and functional independence in the elderly patients with DM admitted to the diabetes center in Boroujen, Iran. Materials & Methods: This cross-sectional study was conducted on 123 elderly patients with DM (age range: 60-74 years), who were selected via non-probability sampling in Boroujen, Iran. After obtaining written informed consent, data were collected using Barthel functional independence scale and brief ageing perception questionnaire (B-APQ) via face-to-face interviews with the subjects (20 minutes) to complete the questionnaires. Results: The mean total score of ageing perception in the patients was 58.21±7.5, which indicated the unfavorable perception of ageing, encompassing 16.1% of the dimension of negative perception of aging. In addition, the mean total score of functional independence was 95.71±4.8, indicating that 52.8% of the subjects had slight dependence, while the lowest number of the patients (11.4%) had moderate dependence. The obtained results of the study indicated an inverse, significant correlation between the total scores of functional independence and perception of aging (P≤0.001; r=-0.76). Conclusion: According to the results, which demonstrated the inverse, significant correlation of the perception of aging and functional independence in the patients, it seems that the awareness of the influential psychological factors in the health and functional capacity and independence of various age groups could help policymakers to adopt preventive strategies for comprehensive geriatric healthcare as a form of holistic care, which in turn results in the implementation of educational and counseling interventions. Therefore, it is recommended that the perception of ageing be enhanced in the elderly through the empowerment of these individuals and increasing their functional independence. Some of the suggested approaches to the reduction of the negative perception of ageing include empowerment education and counseling in order to enhance the positive perception of ageing, thereby helping the elderly in functional independence and health promotion.